ARM Assembly Language with Hardware Experiments - Elahi, Ata; Arjeski, Trevor (Springer International Publishing : Imprint: Springer, 2015)
This book provides a hands-on approach to learning ARM assembly language with the use of a TI microcontroller. The book starts with an introduction to computer architecture and then discusses number systems and digital logic. The text covers ARM Assembly Language, ARM Cortex Architecture and its components, and Hardware Experiments using TILM3S1968. Written for those interested in learning embedded programming using an ARM Microcontroller. ·         Introduces number systems and signal transmission methods   ·         Reviews logic gates, registers, multiplexers, decoders and memory   ·         Provides an overview and examples of ARM instruction set   ·         Uses using Keil development tools for writing and debugging ARM assembly language Programs   ·         Hardware experiments using a Mbed NXP LPC1768 microcontroller; including General Purpose Input/Output (GPIO) configuration, real time clock configuration, binary input to 7-segment display, creating a voltmeter with an analog-to-digital converter, and using a digital-to-analog converter.